2021
DOI: 10.3233/wor-213465
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Swiss ordinance on maternity protection at work in companies in French-speaking Switzerland

Abstract: BACKGROUND: Switzerland’s Ordinance on Maternity Protection at Work (OProMa) requires that companies take the necessary measures to ensure that pregnant employees can continue working without danger. OBJECTIVE: To investigate the extent of compliance with OProMa within companies in French-speaking Switzerland as well as factors which facilitate and obstruct the ordinance’s implementation. METHODS: A stratified random telephone survey of 202 companies from the healthcare and food industry was conducted. Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Publications dealing with factors associated with absence from work at di erent level Publications dealing with interventions aiming at reducing absences from work relying on... National context Social bene t system and insurance policy [4,6,16,39,40] Occupational exposure [6,10,11,14,[16][17][18][19]21,24] Work atmosphere and environment [25][26][27][28][29][30] accommodations at the workplace [5,7,24,27,[41][42][43][44] program targeting managers [48][49][50] information campaigns [51] Health professionnal Role of physician [31][32][33][34] the use of healthcare services [9,23,[45][46][47] Employer Workplaces conditions Symptoms and pathology [5,[10][11][12] Sociodemographic and general health [5,…”
Section: Sociodemographic Characteristics and General Healthmentioning
confidence: 99%
“…Publications dealing with factors associated with absence from work at di erent level Publications dealing with interventions aiming at reducing absences from work relying on... National context Social bene t system and insurance policy [4,6,16,39,40] Occupational exposure [6,10,11,14,[16][17][18][19]21,24] Work atmosphere and environment [25][26][27][28][29][30] accommodations at the workplace [5,7,24,27,[41][42][43][44] program targeting managers [48][49][50] information campaigns [51] Health professionnal Role of physician [31][32][33][34] the use of healthcare services [9,23,[45][46][47] Employer Workplaces conditions Symptoms and pathology [5,[10][11][12] Sociodemographic and general health [5,…”
Section: Sociodemographic Characteristics and General Healthmentioning
confidence: 99%
“…This study was part of a broader research project (Krief et al, 2018) investigating the application of maternity protection measures in Switzerland. In the project's initial phase, managers of 107 healthcare institutions answered a telephone questionnaire investigating their implementation of the OProMa (Abderhalden-Zellweger et al, 2021). As case studies, we decided to focus on experiences of the maternity protection measures in a convenience sample of three healthcare institutions.…”
Section: Participant Selection and Data Collectionmentioning
confidence: 99%
“…Several studies have identified organizations' shortcomings in the implementation of maternity protection measures, including the absence of a risk assessment and the absence, or inadequacy, of workplace accommodation (Adams et al, 2016a(Adams et al, , 2016bLembrechts & Valgaeren, 2010;Rudin et al, 2018). These shortcomings were also observed in the healthcare sector (Abderhalden-Zellweger et al, 2021;Henrotin et al, 2018). As a result, some employees face a dilemma: ask for sick leave to withdraw from a perceived dangerous work environment, with its potentially negative consequences on their career, professional relationships and salary, or work in an environment that is potentially dangerous to their health and that of their unborn child (Malenfant, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the application of these legislations does not appear to be homogenous, and workplaces are not systematically adapted to the needs of pregnant workers and to the protection of their health. In the context of French-speaking Switzerland, a recent study carried out in two occupational sectors shows that only 12% of workers in the health sector and 2% in the food industry benefit from the protection in accordance with the Swiss legislation [9]. Companies apply the legislation in a heterogeneous/partial manner and gynecologists dot not always feel competent in occupational health issues to assess the hazardousness of working conditions of pregnant women [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of French-speaking Switzerland, a recent study carried out in two occupational sectors shows that only 12% of workers in the health sector and 2% in the food industry benefit from the protection in accordance with the Swiss legislation [9]. Companies apply the legislation in a heterogeneous/partial manner and gynecologists dot not always feel competent in occupational health issues to assess the hazardousness of working conditions of pregnant women [5,[9][10][11]. At the international level, publications underline the heterogeneous applications of the legislations surrounding maternity protection at work.…”
Section: Introductionmentioning
confidence: 99%